DETERMINANTS OF SOVEREIGN CREDIT DEFAULT SWAP (CDS) SPREAD: A CASE STUDY OF INDONESIA 2005-2015 - AGUSTINA, ARININGTYAS WIDYASNIA (2015)
This study attempts to fill in the literature gap of emerging markets’ sovereign Credit Default Swap (CDS) by examining determinants of sovereign CDS pricing in one emerging economy, the Republic of Indonesia. Using monthly data during the period of February 2005-April 2015, this study employed two models to capture the contemporaneous and long-term effects of several macroeconomic and market-related variables to the pricing of Indonesia’s USD-denominated sovereign CDS. These models were then examined using multiple regression analysis with Ordinary Least Square (OLS) method. We found that inflation rate, global market sentiments, and global risk aversion had a contemporaneous relationship with Indonesian CDS spread, while foreign exchange reserve, inflation rate, domestic market sentiments and global risk aversion influence Indonesian CDS spread in a one-month lagged period. Further, we also found that Indonesian CDS spread was strongly correlated across time, where a shock in a previous period would still be found in the next period. Overall, results from this study suggest that Indonesian CDS spread is affected by both macroeconomic variables that shape the credit risk of a country as well as other external factors.